Doing Business in Emerging Markets - Cavusgil, S Tamer (SAGE Publications, Ltd. (UK), 2021)
Written by leading scholars, this new third edition provides readers with a comprehensive and authoritative examination of emerging markets across the globe. Fully updated in light of the COVID-19 pandemic and other recent macro drivers, the authors present analytical frameworks, tools and best practice insights to help readers develop a critical understanding of the growth economies presented within the book, alongside their common characteristics, evolution, and significance in the global economy. Making use of original cases encompassing countries including Brazil, China, Russia, Thailand, Turkey and Uzbekistan, the authors explore the unique challenges and opportunities for emerging markets throughout the world today, including the rising middle class, partnering, and negotiation techniques.  This text is essential reading for international business students, researchers and practitioners focused on business in emerging markets.